Pengaruh Budaya Organisasi Terhadap Agilitas Organisasi (Study Pada Fashion X) - Fuzi Fauziyyah; Sri Raharso (Jurnal Riset Bisnis dan Investasi, 2016)
An organization has the characteristic or particular identity for the purpose of uniting its members so as to have an overview of running the organization as reflected by the organizational culture in it. Strong organizational culture is one way to achieve agility, the new management approach to deal with changes. This research aimed to find out how the organizational culture and organizational agility and the influence of organizational culture on organizational agility in the case study at Fashion X. In this research method used quantitative and descriptive method and using questionnaires that distributed to 131 respondents and interviews. The study states that the organizational culture and organizational agility in Fashion X quite good, even though it needs upgrading for adhocracy, hierarchy, and competency. Both variables have strong positive relationship amounted to 0,548 and in Fashion X 30% organizational agility affected by organizational culture. Additionally regression equation Y = 64.323 + 0,657X. Organizational culture can be improved by increasing risk-taking by creating small teams, develop products, gathering, team building to enhance the innovative thought leaders, improving the way for more efficient delivery of goods, execution, product’s strategy, situational leadership, technology, the power of employees, organizational ability, organizational changes, and customer’s services.